Graduation in Public Health in Brazil: Training, professional identity and insertion in the labor market (Research, Society and Development, 2021)
Introduction: The Undergraduate Collective Health Courses (CGSC) emerged with the aim of reducing training time and meeting the need for professionals able to work in the field of public health within the scope of the Unified Health System (SUS). Objective: To analyze publications on CGSC in Brazil in recent years and to characterize them in terms of the main approaches studied. Methodology: This is an integrative literature review. The search for articles occurred in the following databases: Scielo, Lilacs and Scopus. The descriptors collective health, public health and health management were related to the descriptors undergraduate and health. Original articles, available in full, related to the objective of the study, published in the period from 2015 to 2020 in Brazil, were included. The search listed 3,315 articles, however, only 10 articles met the inclusion criteria. Results / discussion: The selected studies were grouped into: 1. Panorama, training and professional identity; 2. Insertion in the job market. The courses present a training profile for the management of health services and systems. The insertion in the job market has been done gradually, around 43% of graduates, most of them in public services occupying management and service management positions and with precarious employment ties. Final considerations: The study was a precursor in the analysis of the original articles, produced on the CGSC in Brazil, allowed the summarization of the researches carried out and brought a current panorama on the theme about the identity and the insertion of these professionals in the job market.